A New Jury Model in the Republic of Korea - REKHOVSKIY, Aleksandr Fedorovich; VOROPAEV, Genadiy Stepanovich (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The paper considers the issue of jury court development in the Republic of Korea in XXI century. The jury system introduction into Korea legislation is looked at. The analysis of the jury in the Republic of Korea is aimed at considering the trend of jury introduction in the countries lacking the experience in this institute implementation. The Korean jury model is of interest as it gives the solution for two main drawbacks of the jury: high costs of a lawsuit and time-consuming court procedures. The reforms being introduced into the Korean law system achieve the main purposes similar to the on-going democratic reforms in Japan. Despite this, the jury in Korea was not just a borrowed jury form which exists in the common-law countries (the USA, Great Britain, etc.). There are some peculiarities in jury specifically typical for South Korea. The requirements for the jury members, jury composition, voting procedure in delivering a verdict are analyzed. The consultative nature of the jury's verdict not being obligatory for the court is emphasized. However, in many cases the jury decisions are similar to the final decision of the court. The court practices in considering the criminal trials with the jury participation are given. The author arrives at the conclusion that jury introduction in the Republic of Korea is a vivid event in the history, influences the law culture and legal awareness of the citizens, which is particularly important for any state to function and to develop the society in an appropriate way. The jury system in the Republic of Korea can be distributed into the countries of the Asian-Pacific region.